The Importance of Pregnancy Checkup for Pregnant Women (Anc K4) in Neighborhood III Baru Ladang Bambu Village, Medan Tuntungan District, 2020 - Nurdiana Manurung; Rizky A. Bakara (Science Midwifery, 2020)
The purpose of this study was to determine the effect of health education by providing counseling materials on condom contraception to couples of childbearing age in the V Village of Baru Ladang Bambu, Medan Tuntungan District. Increasing knowledge of EFA that the use of contraceptives is not for women but men can also be acceptors of family planning, such as the use of condoms, increasing the influence of knowledge of health education by teaching women about the types of contraceptives other than condoms to men. The types and forms of activity of this activity are providing material to EFA about contraceptives and giving explanations to EFA, about a more detailed explanation of condoms. To achieve the objectives of the above activities, activities were carried out, including providing counseling materials on condom contraception to female sex workers, to assist women as users of family planning acceptors..